Companion and free-ranging Bali dogs: Environmental links with personality traits in an endemic dog population of South East Asia. - Luca Corrieri; Marco Adda; Ádám Miklósi; Enikő Kubinyi (PLoS ONE)
Dogs living on Bali Island have been free-ranging for thousands of years. A large group of expatriates sometimes adopt Bali dogs and keep them restricted to their houses and backyards, as is typical in modern western cultures. This provides us with the unique opportunity to compare the personality traits of dogs to their lifestyle either living as human companions or as free-ranging animals, exploring at the same time the impact of demographic variables (such as age, sex, and neutered status) on personality. After controlling for internal consistency of the scales and between-observer variation, we found that free-ranging Bali dogs were rated as less active, less excitable, less aggressive towards animals, and less inclined to chase animals or humans than Bali dogs living as human companions. Among free-ranging dogs, females were found to be more excitable. Females in the whole sample were also more fearful of people. The results of this preliminary study suggest that a change in lifestyle, i.e. being adopted, and living in a confined environment has negative consequences on some canine personality traits, such as activity/excitability, aggression towards animals, and prey drive.